Management of Intrathoracic Sepsis- A Review Article - Rahman, Mostafizur; Khan, Omar Sadeque (Journal of Surgical Sciences, 2013)
DOI: http://dx.doi.org/10.3329/jss.v16i1.14446 Journal of Surgical Sciences (2012) Vol. 16 (1) : 35-38